Origins of the French welfare state : the struggle for social reform in France, 1914-1947 - Dutton, Paul V. (New studies in European history., 2002)
This is the first comprehensive analysis of public and private welfare in France available in English or French, which offers a deeply-researched explanation of how France's welfare state came to be and why the French are so attached to it.